Multiagent paradigm for the agent selection and negotiation in a B2C process - Mazumdar B.D.; Mishra R.B. (My University, 2025)
Multiagent paradigms have been developed for the negotiation and brokering in B2C e-commerce .Few of the models consider the mental states and social settings (trust and reputation) but rarely any model depicts their combination. In this work, we present three mathematical models. First cognitive computational model which is combined model of belief, desire, intention (BDI) model for agent's mental attitudes and social settings; is used for the computation of trust and then index of negotiation which is based on trust and reputation and the second computation model is developed for the computation of business index that characterizes the parameters of some of the business processes, which match the buyer's satisfaction level. The third computation model of utility is used for negotiation between seller and buyer to achieve maximum combined utility increment (CUI) which is the difference of marginal utility gain (MUG) of buyer and marginal utility cost (MUC) of seller. © 2009.